Legalización y disolución de uniones consensuales : un ejemplo del uso de modelos log-lineales para estimar modelos de riesgos en competencia - Gómez de León Cruces, José (El Colegio de México A.C., 1998)
This is a mainly methodological work: a generalization of the so-called proportional risk models to cases of multiple and competing risks. As shall be seen, proportional risk models are an extension of the methodology implied in calculating mortality tables, where the risk function is made to depend on some variables (covariables), as in a regression model. Needless to say, life-table methodology has been, ever since its appearance in the seventeenth century (Halley, 1693), an essential instrument in demographic calculus and analysis. This work points out the utility of these methodological advances in the analysis of demographic data, although they were developed in biostatistics and systems engineering.